The effective hydropower potential of the Mszanka River in South Poland – the course of estimation - Operacz, Agnieszka; Kotowski, Tomasz; Bugajski, Piotr (Lviv Politechnic Publishing House, 2018)
The aim of the paper was to calculate the actual (called “effective”) hydropower potential based on the identification of real possibilities of small hydro power plants realization. As an example river Mszanka in South Poland was chosen. The course of estimation was shown in Polish conditions of law, procedures and environmental barriers. The comparison of estimated values of effective potential was done with theoretical and technical potential.
Keywords: hydropower potential; RES; sustainable management; small HPP